Two competing crack growth mechanisms in very high pressures tubes - Otegui, Luis Jose (2010)
This work addresses the influence of autofrettage in the occurrence of repeated leaks of thick wall straight and curved 4333M4 steel tubes from a high pressure petrochemical reactor, comprised by straight and curved tubes subjected to autofrettage. Recent leaks in straight tubes are due to fatigue transgranular growth of cracks initiating from machining groves in the inner surface, driven by pressure cycles during many years of normal operation. Experimental measurement of residual stresses verified that high temperature service relieved most of the compressive residual stresses imposed by the autofrettage. Previous failures in curved tubes were found to be due to metallurgical susceptibility to intergranular cracking, related to a phenomenon similar to Temper Embrittlement. Repeating autofrettage to mitigate fatigue failures would reproduce the deformation mechanisms that favored intergranular cracking of the tubes. Recently developed life extension strategies include early detection of leaks by acoustic emission and an improved manufacturing method of replacement bends.